How to run successful projects - O'Connell, Fergus (New York : Prentice Hall, 1994)
This book introduces Structured Project Management, a method designed to bring order and rigor to project management processes. It emphasizes people management, built-in self-checking mechanisms, and provides a complete, simple-to-learn approach for successful project execution.
Notes Registration No: 27667 (B$$47.40), 27881 (B$$34.90)
Includes bibliographical references and indexes.
Keywords: Project management; Project management -- Great Britain